Reading Prehistoric Human Tracks Methods & Material - Pastoors, Andreas; Lenssen-Erz, Tilman (Springer Nature, 2021)
This Open Access book explains that after long periods of prehistoric research in which the importance of the archaeological as well as the natural context of rock art has been constantly underestimated, research has now begun to take this context into focus for documentation, analysis, interpretation and understanding. Human footprints are prominent among the long-time under-researched features of the context in caves with rock art. In order to compensate for this neglect an innovative research program has been established several years ago that focuses on the merging of indigenous knowledge and western archaeological science for the benefit of both sides. The book gathers first the methodological diversity in the analysis of human tracks. Here major representatives of anthropological, statistical and traditional approaches feature the multi-layered methods available for the analysis of human tracks. Second it compiles case studies from around the globe of prehistoric human tracks. For the first time, the most important sites which have been found worldwide are published in a single publication. The third focus of this book is on firsthand experiences of researchers with indigenous tracking experts from around the globe, expounding on how archaeological sciencecan benefit from the ancestral knowledge. This book will be of interest to professional archaeologists, graduate students, ecologists, cultural anthropologists and laypeople, especially those focussing on hunting-gathering and pastoralist communities and who appreciate indigenous knowledge.